Experimental and theoretical spectra of layered Li TM oxide cathode materials - Ramesh, N (University of Oxford, 2024)
This data set contains experimental and simulated core-level X-ray absorption spectra of layered Li TM oxide cathode material. These spectra have been background-subtracted, normalised and calibrated to experimental references.